Role of Procalcitonin and C-Reactive Protein As Biomarkers of Infection in Children With Liver Disease. Issue 4 (October 2016) - Bolia, Rishi; Srivastava, Anshu; Marak, Rungmei; Yachha, Surender K.; Poddar, Ujjal
Abstract: Objectives: Early and accurate identification of infection in patients with liver disease is challenging. The present study evaluated the role of procalcitonin (PCT) and C-reactive protein (CRP) as biomarkers of bacterial infection in children with liver disease. Methods: Demographic and clinical data of consecutive children admitted with acute liver failure (ALF) or decompensated chronic liver disease (DCLD) were collected. PCT and CRP were measured within 24 hours of admission. Blood and urine culture, chest x-ray, and ascitic fluid analysis were done. Results: One hundred sixty-four children (113 boys, age 76 [0.5–204] months, ALF 69, DCLD 95) were enrolled. Seventy-seven (47%) had infection. Most common site was ascitic fluid (n = 35), followed by urinary tract (n = 26), pneumonia (n = 22), and blood stream infection (n = 16). Twenty-one children had multiple-site infections, 18 had severe sepsis, and 36 had systemic inflammatory response syndrome. PCT and CRP correlated with infection severity, higher in severe sepsis (8.3 [3.5–38] ng/mL and 4.1 [0.3–13.8] mg/dL) than only infection (0.89 [0.1–8] ng/mL and 1.7 [0.32–24] mg/dL) and no infection (0.3 [0.1–6.75] ng/mL and 0.3 [0.1–4.16 mg/dL]). Systemic inflammatory response syndrome was more common in patients with infection (31/77 vs 5/87, P = 0.00). PCT (>0.5 ng/mL) and CRP (>0.6 mg/dL) performed better in DCLD (AUC of 0.90 and 0.83) compared with patients with ALF (AUC of 0.73 and 0.69). Conclusions: : PCT and CRP are reliable markers of infection and correlate with infection severity in children with liver disease. Their diagnostic accuracy is better in DCLD than ALF cases.